The logo change at Gap North America. Issue 2 (5th May 2016) - Pollach, Irene
Abstract : Synopsis: The case study outlines the strategic, marketing, and branding challenges faced by Gap, a brand within the Gap Inc. house of brands. The case contains a summary of Gap's history, which illustrates the driving forces behind Gap's previous growth, its status as an American iconic brand, and its struggle to stay relevant. This sets the stage for Gap's rebranding exercise, which included an attempt at changing their iconic logo. This case provides students with the opportunity to learn about brand life cycles and the implications of a logo change for brand equity, brand associations, and brand positioning. Research methodology: This research is based on published sources. Relevant courses and levels: The case can be used in courses in strategic brand management, retailing, fashion marketing, marketing communication, or corporate communication at the graduate or advanced undergraduate level. The case will be particularly useful for those who already understand branding and consumer behavior, but who may not have learned anything about rebranding or strategic brand management. It is not suitable for undergraduates who have not studied branding at all.